High-sensitivity temperature sensor based on Mach–Zehnder interferometer filled with dimethyl silicone oil. (1st January 2023) - Zhu, Xiping; Jiang, Chao; Guo, Xiaoshan; Chen, Hailin; Sun, Simei; Liu, Changning
Abstract: In this paper, a high-sensitivity temperature sensor based on the Mach– Zehnder interferometer (MZI) is designed and verified by experiments. The MZI is a splicing structure of 'single mode fiber–multimode fiber–quartz capillary–multimode fiber–single mode fiber'. A microchannel was fabricated on the walls of the capillary by femtosecond laser pulses, and dimethyl silicone oil (DSO) was injected into the capillary by the immersion method. When filled with DSO, the microchannel is sealed with epoxy adhesive to form a MZI temperature sensor. When the ambient temperature changes, the DSO in the capillary of the MZI has a very high thermo-optical effect, resulting in a change in the optical path difference in the MZI and a large wavelength shift in the transmission spectrum of the MZI. Therefore, high temperature sensitivity can be obtained by demodulating the wavelength shift of the MZI transmission spectrum. The experimental results show that the temperature sensitivity of the MZI filled with DSO is 7.421 nm °C −1 in the range of 30 °C–50 °C, which is 297 times that of the MZI without DSO (0.025 nm °C −1 ). In addition, the sensor has a compact structure, robustness, good repeatability and stability.